The Effectiveness of Education and Reminder Messages in Increasing OHI-S, Patient’s Behavior, and Oral Health Literacy in Dental Practice: A Systematic Review of Randomized Controlled Trials - Aurelle Khadeeja Rizany; Jesslyn Christabella; Natasha Natasha; Benso Sulijaya (Indonesian Dental Association, 2023)
According to Basic Health Research, dental and oral health is still one of the main health problems that occur especially in small cities due to lack of accessibility. Poor oral hygiene scores can lead to complex diseases such as caries and periodontal disease. If this condition persists, it will have an impact on aspects of the patient's life such as disruption of productivity, and declining general health of patients, resulting in disruption of social aspects. Until now, no solution can improve the oral health of the community. Whereas Indonesia needs to prepare a competent and healthy workforce to reach Indonesia Gold 2045. Short messages sent by hospitals containing reminders and education have the potential to increase public awareness of the importance of compliance in maintaining dental and oral hygiene. To analyze the implementation of short messages in support of modification of reminders and education in dental practice. The main references were taken from the PubMed, Science Direct, and Wiley databases last accessed on 16 April 2022. 31 search results that had been filtered using PRISMA 2009 became the source with 5 main data that met the inclusion criteria. in the form of clinical studies in the form of randomized controlled trials that have been processed using the study tool from the NIH. From a systematic study, it was found that short messages can be used as reminders and education in the fields of public dental health, pediatric dentistry, orthodontics, and periodontics. This method is carried out with follow-up and evaluation for up to 6 months. Countries such as France, Italy, India, America, and Japan have used this method. The main outcome of this study was an improvement in the oral hygiene score (OHI-S), behavior, and oral health literacy. The use of reminders in the form of short messages has the potential to increase public awareness of the importance of compliance in maintaining dental and oral hygiene. The short message approach as a dental support service has proven to have many advantages and can be implemented in Indonesia.